2017
DOI: 10.1080/09513590.2017.1380182
|View full text |Cite
|
Sign up to set email alerts
|

Administration of prednisolone and low molecular weight heparin in patients with repeated implantation failures: a cohort study

Abstract: Conflicting results exist for low molecular weight heparin (LMWH) and prednisolone when tested as separate adjuncts for the improvement of the clinical outcomes in patients with repeated implantation failures (RIF) undergoing IVF/ICSI treatment. Through a cohort study, we evaluated the combined effect of both drugs on pregnancy parameters in 115 women with RIF. Clinical pregnancy rate was the primary end point while the sample size was calculated through the results of a pilot study. Clinical and IVF cycle cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…44 On the other hand, as previously underlined, heparin has also been considered as an adjunct drug in assisted reproduction, in particular during peri-implantation, in order to increase the rate of successful pregnancies. [45][46][47] LMWHs as tinzaparin and enoxaparin may also modulate the expression of heparin binding epidermal growth factor (HB-EGF) in addition an effect on decidual and endometrial stromal cells has been reported. 48 Furthermore, heparin, similarly to heparin sulfate proteoglycans or HB-EGF, should be involved in blastocyst adhesion, invasion and proliferation.…”
Section: Lmwh In Ivf Proceduresmentioning
confidence: 99%
“…44 On the other hand, as previously underlined, heparin has also been considered as an adjunct drug in assisted reproduction, in particular during peri-implantation, in order to increase the rate of successful pregnancies. [45][46][47] LMWHs as tinzaparin and enoxaparin may also modulate the expression of heparin binding epidermal growth factor (HB-EGF) in addition an effect on decidual and endometrial stromal cells has been reported. 48 Furthermore, heparin, similarly to heparin sulfate proteoglycans or HB-EGF, should be involved in blastocyst adhesion, invasion and proliferation.…”
Section: Lmwh In Ivf Proceduresmentioning
confidence: 99%
“…Overall, this study demonstrates that prednisolone alters decidualized hESF and altered decidual-trophoblast interactions. The clinical consequences of these changes are unknown, however, as all available data suggests that corticosteroid administration has no beneficial effect for IVF (Kaye et al, 2017;Mohammadi Yeganeh et al, 2018), RPL (Tang et al, 2013;Cooper et al, 2019;Woon et al, 2020), or repeated implantation failure (Siristatidis et al, 2018) and the emerging evidence that corticosteroid use during pregnancy may be associated with poor obstetrical outcomes (Boyd et al, 2015;Bandoli et al, 2017), offlabel use of corticosteroids, in particular prednisolone, during the period of decidualization (secretory phase of the menstrual cycle and the 1st trimester), should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective pilot study confirmed that prednisolone was useful in patients with at least two previous IVF failures and serum antiovarian antibody [ 23 ]. However, a recent retrospective cohort study demonstrated that the administration of prednisolone with LMWH in women with RIF (two or more failed fresh IVF or ICSI cycles followed by embryo transfer) does not improve pregnancy outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the meta-analysis published in 2013, the live birth rate was estimated to be 16.1% in women with 3 or more failed embryo transfer cycles [ 16 ]. In women with 2 or more failed embryo transfer cycles, the live birth rate varied from 15.5 to 29% [ 17 19 ]. It is reported that the combined administration of prednisone and low molecular weight heparin or aspirin can improve live birth rate by 10.8–14% [ 17 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation